Given D.E is
"(x-1)^2 y'' - 2(x-1)y' + 2y = (x-1)^2 \\:,y(0) = 3, y'(0) = 6"Notice that solution of homogeneious equation "(x-1)^2 y'' - 2(x-1)y' + 2y =0" is
"y_1=(x-1)"We find second independent solution fron Liouville formula is
"W_{y_1y_2}(x)=\\begin{vmatrix}\n y_1&y_2\\\\y_1'&y_2'\n\\end{vmatrix}=C_1e^{-\\int \\frac{-2(x-1)}{(x-1)^2}dx}=C_1(x-1)^2"Thus,
"\\dfrac{y_1y_2'-y_1'y_2}{y_1^2}=C_1\\frac{(x-1)^2}{(x-1)^2}=C_1\\implies (\\frac{y_2}{y_1})'=C_1\\\\\n\\implies y_2=C_1(x-1)^2+C_2(x-1)"Hence, general solution of homogeneous equation is
"y_o(x)=C_1(x-1)^2+C_2(x-1)"Now, using methood of variation of parameters and construct general solution of inhomogeneous equation ,
"y_1\n(\nx\n)\n \\:\\text{and}\\:\ny_\n2\n(\nx\n)\n:\ny_\n0\n(\nx\n)\n=\nC_\n1\ny_\n1\n(\nx\n)\n+\nC_\n2\ny_\n2\n(\nx\n)\n,\nwhere \\:\nC_\n1\n,\nC_\n2\n \\:\\text{are arbitrary constants.}"
Thus,
"\\text{The derivatives of the unknown functions }\nC_\n1\n(\nx\n)\n \\&\nC_\n2\n(\nx\n)\\:\n\\\\ \\text{can be determined from the system of equations}"
Hence,
"{{C\u2019_1}\\left( x \\right) = \u2013 \\frac{{{y_2}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}},\\;\\;}\\kern-0.3pt\n{{C\u2019_2}\\left( x \\right) = \\frac{{{y_1}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}}.}"
Furthermore, knowing the derivatives of "{C\u2019_1}\\left( x \\right)" and "{C\u2019_2}\\left( x \\right)" ,one can find the "C_1(x)\\& C_2(x)" Thus,
"{{{C_1}\\left( x \\right) }={ \u2013 \\int {\\frac{{{y_2}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}}dx} }+{ {A_1},\\;\\;}}\\kern-0.3pt {{{C_2}\\left( x \\right) }={ \\int {\\frac{{{y_1}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}}dx} }+{ {A_2}}}"where"A_1\\&A_2" are constants of integration.Then the general solution of the original nonhomogeneous equation will be expressed by the formula
Where,
"{Y\\left( x \\right) }\n= {{y_2}\\left( x \\right)\\int {\\frac{{{y_1}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}}dx} }\n\u2013 {{y_1}\\left( x \\right)\\int {\\frac{{{y_2}\\left( x \\right)f\\left( x \\right)}}{{{W_{{y_1},{y_2}}}\\left( x \\right)}}dx} }"Thus, from above fact by putting "f(x)=(x-1)^2" and solving exactly as above we get the general solution is
"C_1(x-1)-(x+\\ln(x-1))(x-1)+C_2x(x-1)+x\\ln(x-1)(x-1)"Thus particular solution is
"- (x-1)(10x+\\ln(x-1)-x\\ln(x - 1)+3-\\pi i + \\pi xi)"
Comments
Leave a comment